2004
DOI: 10.1124/dmd.32.1.149
|View full text |Cite
|
Sign up to set email alerts
|

FUNCTIONAL CHARACTERIZATION OF FOUR NATURALLY OCCURRING VARIANTS OF HUMAN PREGNANE X RECEPTOR (PXR): ONE VARIANT CAUSES DRAMATIC LOSS OF BOTH DNA BINDING ACTIVITY AND THE TRANSACTIVATION OF THE CYP3A4 PROMOTER/ENHANCER REGION

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Metabolism of administered drugs is determined by expression and activity of many drug-metabolizing enzymes, such as the cytochrome P450 (P450s) family members. Pregnane X receptor (PXR) is a master transcriptional regulator of many drug/xenobiotic-metabolizing enzymes, including P450s and drug transporters. In this study, we describe the functional analysis of four naturally occurring human PXR (hPXR) variants (R98C, R148Q, R381W, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…On the other hand, literature on the cellular localization of PXR provides conflicting findings. Based on immunostaining data, some groups have reported that hPXR is exclusively localized in the nucleus (Kawana et al, 2003;Koyano et al, 2004), but other groups provided contradictory results (Kawana et al, 2003;Squires et al, 2004). For example, Squires et al (2004) showed in mouse liver that PXR was localized in the cytoplasm and only translocated into the nucleus when PXR was activated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, literature on the cellular localization of PXR provides conflicting findings. Based on immunostaining data, some groups have reported that hPXR is exclusively localized in the nucleus (Kawana et al, 2003;Koyano et al, 2004), but other groups provided contradictory results (Kawana et al, 2003;Squires et al, 2004). For example, Squires et al (2004) showed in mouse liver that PXR was localized in the cytoplasm and only translocated into the nucleus when PXR was activated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these natural PXR protein variants may play a role in the observed interindividual variability of CYP3A4 expression and may be involved in rare, atypical responses to drugs or altered sensitivities to carcinogens (Hustert et al, 2001). Four additional, naturally occurring hPXR variants (R98C, R148Q, R381W, and I403V) have been identified and their functions characterized recently by Koyano et al (2004). An important finding was that the variant R98C, which alters an amino acid immediately after the fourth cysteine residue of the second zinc finger of the DBD, caused dramatic loss of both DNA binding activity and the transactivation of the CYP3A4 promoter/enhancer region.…”
Section: Downloaded Frommentioning
confidence: 94%
“…Recent studies indicate that the overlap in PXR and CAR target genes extends well beyond the members of the CYP3A, CYP2C, GSTs, UGTs, and the canalicular ABCC2 transporter (29). Functional polymorphisms have been identified for both PXR and CAR, but interethnic genetic variation in humans has not yet been well characterized (3,30). Interethnic differences in PXR haplotype constitution as observed in the present report suggest that future studies should also take into consideration polymorphisms in other coregulators such as CAR while investigating for interethnic and interindividual variations in drug disposition related to PXR target genes.…”
Section: Discussionmentioning
confidence: 99%